THE EFFECT OF MATERNAL CARE (ACOUSTIC STIMULUS) ON EMBRYONIC DEVELOPMENT AND HATCHING MUSCLE OF BROILER CHICKENS. - M. Abdulateef, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was carried out at hatcheries and laboratories of Animal Production Department - College of Agricultural Sciences - University of Sulaymaniyah, by using 240 fertilized egg (Ross 308), distributed to four treatments,T1= first treatment control treatment without hearing any sound, T2= second treatment hearing the hen call , T3= treatment third hearing  chicks hatched call and T4= treatment fourth hearing chick with hen call, each treatment divided to three replicates and each repeater 20 eggs, hearing the sound from the age of 5 days form incubation and until the day of hatching, the sound was given for a period of 15 minutes per hour in 24 hours, the results showing: significantly (P≤0.01)  improvement in embryonic development traits for all experimental treatments in embryonic test second and third compared with the control treatment, significantly (P≤0.01) improvement in the quality specifications for the hatching muscle and histological test for all experimental treatments compared with control treatment.